Growth and Yield Component of Two Varieties of Soybeans (Glycine max L. Merril) in Some Types of Amelioration in Ultisol - Siska Indriani; Dotti Suryati; Hesti Pujiwati; Prasetyo Prasetyo; Entang Inoriah Sukarjo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2021)
Soybeans are the third most important commodity after rice and corn. Soybeans are also a commodity rich in protein. Soy serves as a very important source of vegetable protein to improve people's nutrition because in addition to being safe for health is also relatively cheap compared to animal protein sources. Ultisol has a wide distribution but has constraints to be used as a medium of cultivation plants. The addition of some types of ameliorating or soil reformers such as chicken manure, cow manure, and composting oil palm bunches (OPB) is expected to overcome ultisol fertility. The purpose of this study was to compare the influence of varieties on the growth and component of soybean crop yields in Ultisol, compare the influence of ameliorating type on the growth and component of soybean crop yields in Ultisol, and get the interaction between the type of varieties with the type of amelioration to the growth and components of soybean crop yields in Ultisol. The research was conducted from February to May 2019 in the experimental garden of Integrated Agricultural Zone of the Faculty of Agriculture UNIB Medan Baru, Bengkulu City. This study used a Complete Randomized Design (CRD) that was compiled factorially with 3 times. The first factor is the variety type Anjasmoro and Gepak Kuning, the second factor of amelioration type is control (without amelioration), chicken manure 15 tons ha-1, cow manure 15 tons ha-1, husks burn 15 tons ha-1, and compost oil palm bunches (OPB) 15 tons ha-1. The results showed that the Gepak Kuning variety showed better growth than the Anjasmoro variety while the Anjasmoro variety showed better results than the Gepak Kuning variety. Chicken manure is the best type of amelioration compared to cow manure, rice husks, and compost OPB against the growth and component of soybean yields in Ultisol, and there is interaction in the Gepak Kuning variety with chicken manure amelioration and compost OPB.